Interconnected electrocatalytic Pt-metal networks by plasma treatment of nanoparticle-peptide fibril assemblies. Issue 10 (13th February 2019) - Bandak, J.; Petzold, J.; Hatahet, H.; Prager, A.; Kersting, B.; Elsner, Ch.; Abel, B.
Abstract : Noble metal catalysts possess outstanding catalytic behaviors, photocatalysis, electrocatalysis and many other applications, when interconnected via peptide fibrils. Abstract : Noble metal catalysts possess outstanding catalytic behaviors in organic reactions, photocatalysis, electrocatalysis and many other applications. Peptide fibrils are used for the controllable nanostructuring of metal nanoparticles with specific sizes, shapes and high-surface area structures. The degradation of these fibrils with O2 -plasma yields interconnected networks of nanoparticles, similar to metallic nanowires. Herein, platinum nanoparticles (Pt-NPs) were synthesized by reduction using VUV excimer radiation. The particle size was characterized by dynamic light scattering (DLS). Due to agglomeration, the metal nanoparticles were stabilized using poly(vinyl pyrrolidone) (PVP) and the same synthesis procedure. The influence of the polymer PVP molecular weight ( M wt ), PVP concentration ( C p ) and VUV irradiation time on platinum nanoparticle size was investigated. Small (2–3 nm) Pt-NPs are formed in the case of PVP with M wt = 10 000 g mol −1 . With increasing PVP M wt, decreasing PVP concentration and shorter irradiation times, larger sized nanoparticles appear. The applicability of templated platinum nanoparticles, both the PVP-stabilized and non-stabilized Pt-NPs, immobilized via electrostatic interactions on the solid phase-synthesized aniline-GGAAKLVFF (AFP) peptide fibrils was investigated to serve as possible electrode material. The plasma treatment of the nanoparticle-fibril-assemblies was also studied as a novel technique. The Pt-NPs-AFP fibrils and the PVP-stabilized-Pt-NPs-AFP fibrils nanohybrids were employed to modify electrodes and then subjected to O2 -plasma treatment. These O2 -plasma treated/modified electrodes exhibited high electrocatalytic activities towards oxygen reduction in cyclic voltammetry measurements. Thus, the aforementioned nanocomposites hold great potential for polymer electrolyte fuel cells and other electrochemical applications in miniature devices and microfluidic chips.